Transformational Leadership by the Leader of Muhammadiyah Region of Central Kalimantan - Wahyudi, Jaemi (PT Mattawang Mediatama Solution, 2024)
Muhammadiyah leadership covers the central, regional, branch, and general levels. This research focuses on transformational leadership within the Central Kalimantan Muhammadiyah organization with a model based on four points, namely the Influence of Idealism, Inspirational Motivation, Intellectual Stimulus, and Individual Consideration. The research method used in this research is a qualitative descriptive method with data collection techniques obtained from literature studies, interviews, and observations. The research results show that transformational leadership works quite well based on four points, namely the Influence of Idealism, Inspirational Motivation, Intellectual Stimulus, and Individual Consideration. All of these points have worked well in the context of the Muhammadiyah organization progress in Central Kalimantan